Diabetic self-care practice & health-related quality of life of type 2 DM patients - Lamonge, Annastasia Sintia
In the Philippines, Diabetes Mellitus (DM) occupies the 8th rank among the leading causes of mortality from 1990 to 2005, according to the National Nutrition and Health Surveys (NNHes, 2008, 2003). The prevalence of high fasting blood sugar (FBS) increased from 3.4% in 2003 to 4.8% in 2008. An important treatment strategy is to enable the patients to live as healthy persons live, while preventing complications through appropriate treatment and personal management (self-care) to control her/his blood glucose; and to achieve a good quality of life. DM requires regular-continuous treatments and education in order to improve self-care ability of the patient to monitor his/her own condition. For the nurse, as part of health team, self-care of diabetes patient becomes the focus of nursing intervention in controlling blood glucose; and help improve health related quality of life (HRQOL). By knowing and understanding the correlation between self-care practices and HRQoL, nurses can develop nursing care plans for health education and health maintenance. Therefore the purpose of this study is to determine the correlation between the diabetic self-care practice (diet, exercise, glucose monitoring, medication taking, foot care and smoking) and health related-quality of life (physical health and socio-mental health) of Type 2 DM patients. -- The research design used was descriptive correlation. One hundred twenty (n=126) respondents were recruited from the Outpatient Department-Philippine General Hospital (Department of Family Medicine and Department of Medicine). The sampling method was purposive sampling with the following inclusion criteria: have type 2 DM, diagnosed by the physician; at least 2 year or more with DM (2 year); patient attends the OPD-PGH; adult person (Age >18 years old); With oral hypoglycemic agents (OHAs) only; No known dementia; have ability to understand and speak English or Filipino; consenting to participate; no DM complication; and Filipino (male and female). The tools used were ‘The Summary of Diabetes Self-Care Activities’ (SDSCA) and Short Form 23 version 2 (SF36v2). This study was granted approval by the UP Manila Research Ethics Boards (UPMREB). Permission from Philippine General Hospital to conduct the study in OPD-PGH was also obtained. Informed consent form was approved by the UPM REB and the dignity of participants has been highly respected. Chi-square (x²) was used to determine the correlation between variables. -- Majority of respondents are above 60 years old, female, married, reached high school level of education, unemployed, low income and low family support, had DM for 2-5 years and at least has one co-morbidity. Respondents in this study had best self-care practice in taking medication and had worse self-care practice in blood glucose monitoring. Regarding health- related quality of life (HRQOL), the respondents in this study had better HRQoL in mental domain as compared to physical counterpart. This study reveals a positive correlation between general diet, medication and HRQoL. Those able to perform good self-care practice in general diet and taking medication tended to have higher HRQoL in areas of physical health (physical functioning, bodily pain and general health) and mental health domains (vitality and social functioning). There is also a negative correlation between smoking and HRQoL. Those who smoke had better HRQoL especially in bodily pain, using smoking behavior as a coping mechanism. No significant correlation was found between specific diet, blood sugar test, physical activity, foot care and HRQoL. -- In this study self-care practice is characterized by the capability to follow an eating plan (general diet) and taking medication. Health related quality of life relates to the capacity of the individual to function adequately to perform daily activities (physical health), social function and emotional roles (socio-mental health). Self-awareness and family support are two important points that help explain the ability of respondents to comfy and perform good self-care practice. This has shown to be associated with physical and socio-mental health of HRQoL.